Soil Test Based Fertilizer Prescriptions under IPNS for Rice-Rice Cropping Sequence in Inceptisol of Puducherry - M. Vetrivel, R. Sankar, K. Coumaravel and Pradip Dey, U. Bagavathi Ammal*, L. Venkatakrishnan (Journal of the Indian Society of Soil Science, 2021)
To develop the fertilizer prescription equations based on soil test crop response approach for rice-rice, field experiments were conducted at farmer’s field in Karikalampakkam village, Puducherry, during 2015-2016. Soil test data, yield and NPK uptake by rice-rice were used for obtaining four important basic parameters viz., nutrient required to produce one quintal of rice, contribution of nutrients from fertilizers, contribution of nutrients from soil and contribution of nutrients from farmyard manure (FYM) (% CFYM) for both rice crops. The per cent contribution of nutrients from soil (CS), fertilizer (CF), and FYM (CFYM) were found to be 19.15, 45.90 and 23.27 for N, 12.13, 40.16 and 26.98 for P2O5 and 13.76, 79.64 and 41.07 for K2O, respectively for rice (cv.white ponni). The same for the rice (cv.ADT 45) was 13.48, 40.46 and 34.26 for N, 15.81, 44.64 and 19.89 for P2O5 and 10.48, 58.60 and 41.51 for K2O, respectively. Fertilizer prescription equations were developed and nomograms were formulated based on the equations for a range of soil test values and desired yield target for rice. Under NPK + FYM @12.5 t ha-1, 47, 29, 34 and 41, 22 and 27 kg ha-1 of fertilizer N, P2O5 and K2O, respectively could be saved for attaining target yield of 70 q ha-1 for rice cv. white ponni and cv.ADT 45 as compared to NPK fertilizers alone.